Investigating the benefits of transactional analysis in conflict management - Donoghue, Amy (2015)
This dissertation looks into the current literature on behaviour management in England’s secondary schools, from media coverage to policy to psychology. A focus on therapeutic education and Transactional Analysis then allows for small scale research with a year eight form group to find out if learning about and applying Transactional Analysis has any benefits or potential benefits for conflict management. The results show a small number of benefits, and few disadvantages, but gained a positive response from the participants indicating that they wish to see more people learn about the theories. 2. Key Words Transactional Analysis, Behaviour Management, Ego States, Form Tutor, Qualitative Methods, Action Research, Therapeutic Education, Conflict, Pupil Voice